Hexokinase, Malate Dehydrogenase, Fluorescent Esterase and Malic Enzyme Polymorphisms in the Cocoa Pod Borer, Conopomorpha cramerella (Snellen) - Tan, Soon Guan; Muhamad Awang, Rita; Gan, Yik Yuen; Sinha, Rita (1988)
Cocoa pod borers collected in the field from Tawau, Sabah and from Sua Betong, Negeri Sembilan and rambutan fruit borers collected from Puchong and the campus of Universiti Pertanian Malaysia (UPM) in Serdang, Selangor, Malaysia were analysed by polyacrylamide gel electrophoresis. Hexokinase was found to be polymorphic in the UPM population, malate dehydrogenase in the Tawau, Sua Betong and UPM populations and fluorescent esterase and malic enzyme were polymorphic in all four populations.